2014
DOI: 10.1097/hnp.0000000000000016
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Analysis of the Use of Complementary and Alternative Medicine in Turkish Patients with Rheumatoid Arthritis

Abstract: The purpose of this study was to examine the complementary and alternative medicine (CAM) use in patients with rheumatoid arthritis living in different regions and cities of Turkey as well as the factors affecting the use of CAM modalities. Planned as a descriptive and cross-sectional study, this research was conducted as a study covering the rheumatology units of 10 university and 4 state hospitals in Turkey. A total of 594 patients meeting the research inclusion criteria comprised the sample. It was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
1
16
2
Order By: Relevance
“…CAM use is common in patients with chronic disease, and the frequency of its use in RA has been well described, especially in traditional Asian societies. [11][12][13]30,31 Singapore is a developed country with good healthcare facilities and outcomes; yet traditional beliefs and therapies remain deeply ingrained, with widespread practice of and belief in CAM, especially in patients with chronic musculoskeletal disease or chronic pain. CAM users were more likely to be older, Chinese and non-English speaking.…”
Section: Discussionmentioning
confidence: 99%
“…CAM use is common in patients with chronic disease, and the frequency of its use in RA has been well described, especially in traditional Asian societies. [11][12][13]30,31 Singapore is a developed country with good healthcare facilities and outcomes; yet traditional beliefs and therapies remain deeply ingrained, with widespread practice of and belief in CAM, especially in patients with chronic musculoskeletal disease or chronic pain. CAM users were more likely to be older, Chinese and non-English speaking.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies did not have a separate RA data analysis, but >50% of the study population were patients with RA (16,21,28). Most of the studies acquired their data via an in-person questionnaire-based interview (12 of 23), 2 were self-administered surveys (22,30), 1 was a telephone interview (18), 2 were mailed (19,27), and 6 did not specify (15,17,26,33,36,37). A majority of the studies verified the RA diagnosis from the provider or from chart review (n = 15).…”
Section: Resultsmentioning
confidence: 99%
“…For example, vitamins and minerals were included in overall NDS use in a minority of studies (26), while in other studies, use of herbal remedies or traditional forms of herbal medicine were reported separately from NDS (16,21,24,27,28,33). For example, vitamins and minerals were included in overall NDS use in a minority of studies (26), while in other studies, use of herbal remedies or traditional forms of herbal medicine were reported separately from NDS (16,21,24,27,28,33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations